Successful Regeneration and Characterization of Anther Derived Rice Hybrid Plants from O. Sativa L. X O. Rufipogon Griff. - Sah, Bindeshwar Prasad; Niroula, Raj Kumar (Scientific World, 2010)
Doubled haploid regenerated through anther culture of wide cross rice hybrids is one of the potential tools to produce various useful genetic and cytogenetic stocks for molecular studies. In this study, an interspecific hybrid derived from Oryza sativa and O. rufipogon was subjected to anther culture with the aim to regenerate doubled haploid population for their characterization. A total of 21 green and 31 albino plants were obtained from 1904 anthers of O. sativa cv. Himali x O. rufipogon. Six types of androclonal variants were identified based on morphology and panicle characteristics of regenerated plants. Among 21 plants, only six were found diploid with partially fertility. Despite the sterility and preponderance of wild traits, some of the plants showed useful traits such as increased in panicle and spikelet length, reduced shattering and awning, and large size anther as in O. rufipogon. Two of the regenerants were superior for panicle related traits over either parent. The genotyping study using SSR markers also revealed the substantial variation among regenerants. At least three allelic variants were recorded among individual plants based on our preliminary study. The regenerated doubled haploid plants showed large amount of useful variation both at phenotype and molecular level and they can be exploited to enrich the current rice gene pool. Key words: Anther culturability; Albino; Androclon; Calli; Meiosis; SSR marker. DOI: 10.3126/sw.v5i5.2649 Scientific World, Vol. 5, No. 5, July 2007 14-18